MASALAH PELESTARIAN GUA-GUA PENGUBURAN DI KABUPATEN TABALONG, KALSEL - Sugiyanto, Bambang (Naditira Widya, 2006)
The grave-caves, which are found abundantly iQ the karst environment of Tabalong, especially in Haruai and Muarauya, are presently ruined: The damage is caused by the change of karst environment. Such change is contributed by the extensive illegal logging and limestone mining for establishing roads and houses. The interior of caves are also damaged by immense guano digs. Since grave-caves present values of cultural history, they are protected under the Law of Items of Cultural Property. Nevertheless, the facts indicate neither the government nor the community of Tabalong successfully protect its natural and cultural assets. Everyone should be receptive toward the preseNation of karst environment whether flora, fauna, caves or rock-shelters. Therefore, practical steps to preseNe this specific environment are crucial and have to take place immediately. Established plans based on joint programs among stakeholders may solve the preseNation problems on karst environment including the caves.